The employment market for librarians and information professionals in the top 500 corporations in Metro Manila - Calimag, Delia B. 1952- (1997)
A questionnaire, comprising two parts, was the instrument used in gathering data. Two hundred fifty respondents were chosen by drawing lots. There were 126 questionnaires returned, where percentages were computed using LOTUS. Only 86, however, were considered valid for the statistical treatment of data using the Statistical Package for Social Sciences (SPSS) and Analysis of Variance (ANOVA).
A study about the employment market for librarians and information professionals (LIPs) in the top 500 corporations in Metro Manila was conducted to fulfill a three-fold mission: 1) to determine whether the job opportunities for LIPs in the corporate world of work; 2) to ascertain the skills, educational and personal qualifications required by the employers; and 3) to determine in which corporate units/functions and in what types of business the professional services and expertise of LIPs are needed most.
It can be inferred from the data that there is an open employment market for LIPs and LIPs are needed to fill in the job vacancies tha tthe top 500 corporations have.
The findings indicate that there is a very positive employment market potential for LIPs in the top 500 corporations in Metro Manila; computer knowledge is the primary skill the employers required, and a BS degree in LIS and Computer/Information Science satisfy the educational qualifications required. LIPs are most needed in Library and information centers as well as in database design and management. Observations show that LIPs are prefered for work in Banking and Finance, Manufacturing, Community, Social, Personal Services and Trading (wholesale and retail) types of business.
The study recommends the training of more LIPs, honed with the skills, personal and educational qualifications required by the existing employment market.
Computer print-out.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Vita.
Keywords: Librarians -- Employment -- Philippines; Corporations -- Philippines -- Manila metropolitan area; Labor market -- Philippines; Librarians -- Supply and demand. -- Philippines